Corporate Sustainability Behavior and Tax Avoidance: Investigating ESG Disclosure, ESG Controversies, and Profitability Interaction - Dewi Khofsoh; Badingatus Solikhah (University of Merdeka Malang, 2026)
This study aims to examine the effects of ESG disclosure, ESG controversies, and capital intensity on tax avoidance, with profitability as a moderating variable. Tax avoidance remains a critical issue affecting tax performance in Indonesia, while the increasing adoption of Environmental, Social, and Governance (ESG) practices raises questions regarding corporate tax behavior. Therefore, this study is important for examining the effects of these factors. The study utilizes secondary data from 362 firm-year observations of non-financial companies listed on the Indonesia Stock Exchange during the 2015–2024 period, sourced from Refinitiv Eikon. The analysis was conducted using Moderated Regression Analysis (MRA) with a Fixed Effects Model (FEM) approach in EViews 12. The results indicate that ESG disclosure and capital intensity have a negative effect on tax avoidance, while ESG controversies has no significant effect. Furthermore, profitability weakens the negative effects of ESG disclosure and capital intensity on tax avoidance and moderates the effect of ESG controversies on tax avoidance. These findings indicate that companies with high profitability tend to engage in tax avoidance even with good ESG disclosure, yet reduce tax avoidance when ESG controversies arise. Therefore, adaptive oversight and strengthened corporate governance are necessary.